Pengaruh Berkumur Rebusan Daun Binahong (Anredera cordifolia) Terhadap pH Saliva - Welliam, Desih; Erfiani, Mery; Asmawati, Asmawati; Kelfin, Kelfin (Poltekkes Kemenkes Bandung, 2025)
Saliva is produced by the salivary glands in the oral cavity, with an average daily secretion of approximately 700 mL. The normal pH of saliva ranges from 6 to 7 and can be influenced by various stimuli, including taste. Binahong (Anredera cordifolia) is a medicinal plant that grows in both lowland and highland areas. Its leaves are commonly used in traditional medicine due to their content of bioactive compounds such as saponins, flavonoids, polyphenols, and triterpenoids. This study aimed to determine the effect of gargling with boiled binahong leaf solution on salivary pH among dental health students. A quasi-experimental study with a one-group pretest–posttest design was conducted involving 44 participants selected using simple random sampling. Salivary pH was measured before and after gargling with the binahong leaf decoction. Data were analyzed using the Wilcoxon signed-rank test. The results showed a significant increase in salivary pH after gargling with the binahong leaf solution (p = 0.000; p < 0.05), indicating a statistically significant difference between pretest and posttest measurements. In conclusion, gargling with boiled binahong leaves has a significant effect on increasing salivary pH and may serve as a non-pharmacological alternative to support oral health.